PERAN KELOMPOK USAHA BERSAMA (KUBE) DALAM PEMBERDAYAAN MASYARAKAT NELAYAN DI DESA ALUE NAGA KECAMATAN SYIAH KUALA KOTA BANDA ACEH - Juaris; Wahidi, Jhon; Saprijal; Syahroni, Faez (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2023)
The Joint Business Group (KUBE) is one of the fishing community institutions that has a role in developing fisheries and empowerment businesses. KUBE as a non governmental organization to improve the insight and competence of its members in preparing planning, management, and financial arrangements to increase fishermen's income. The purpose of the study was to determine the role of the joint business group (KUBE) in empowering fishing communities in building awareness of the Alu Naga village community. The study used descriptive qualitative research types, observational data collection techniques, interviews. Technical data analysis, data presentation, data verification, and conclusion. The results showed that KUBE provided financial assistance, socialization, training, bout assistance. open opportunities in running a business, increase knowledge and skills in catching fish and so on. Meanwhile, efforts to increase awareness of the fishing community are to make regular extension activities and optimize the capacity of potential fishermen groups to be developed, form fishermen institutions, care for the coastal ecosystem environment, training on the use of fishing technology tools, create new livelihoods as a form of increasing the income of the Alu Naga village community